Teori Oligarki Winters Atas Penambangan Batubara Di Kalimantan Timur - Anita Febriani; Dilla Janu Istanti; Ponco Wibowo (CICES (Cyberpreneurship Innovative and Creative Exact and Social Science), 2021)
Oligarchy portrait occurs in the process of coal mining in East Kalimantan. Many of the power-holding elites are involved in collaborating to become a mining resource chain in East Kalimantan. The Sexi Killer film by WatchDoc Documentary provides a clear picture of how the elite was involved in becoming coal mining players in East Kalimantan. Coal mining does not necessarily bring prosperity to the surrounding community but instead brings about various environmental disasters. Several names of the ruling elite were dragged into the circle of mining business practices. Jefri A. Winters' oligarchic theory can explain why this portrait can occur. Through authority, the elites control material resources to increase wealth and maintain their social position. Democracy seems to have slipped into an oligarchic circle. The elites control material resources to increase wealth and maintain their social position. The oligarchy seen in the Soeharto era did not just disappear. Oligarchy develops in a different form. The oligarchy during the Soeharto era was a sultanic oligarchy, now it has transformed into an oligarchy of collective rulers.